Prevalence of depression and its associated factors among patients with confirmed COVID-19 in Makkah, Saudi Arabia - Alqurashi, Eid; Aldobyany, Ahmad; Touman, Abdelfattah; Alqahtani, Abdullah; Alsaggaf, Rajaa; Alnashiwaaty, Omar; Ghaleb, Nabil; Mabar, Hanan; Albanna, Amr S. (Frontiers in Psychiatry, 2022)
Background In early December 2019, a cluster of acute pneumonia of viral etiology has been identified in Wuhan, China. Later on, it has been named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that caused worldwide pandemic. This pandemic triggered an unprecedented health related psychiatric sequalae. We aim in this study to evaluate the prevalence of depression and its associated factors in COVID-19 confirmed patients. Methodology This is a cross sectional study assessing the degree of depression and associated factors among confirmed COVID-19 patients. Adult patients more than 18 years old who have been diagnosed with PCR confirmed COVID-19 and managed in hospital, home or at hotel were involved. A self‑administered online questionnaire based on Patient Health Questionnaire PHQ-9 Quick Depression Assessment questionnaire was used. Result A total of 143 subjects completed PHQ-9 questionnaire. The prevalence of moderate to severe depression was 34%. Prevalence of depression was positively associated with female gender (p value = 0.013). Location of COVID-19 management and financial status did not affect the prevalence of depression. Conclusion The prevalence of depression among COVID-19 patients is high, underscore the importance of active screening and management of depression in this population.